Perceived Packaging, Perceived Value, Perceived Quality dan Purchase Intention pada Tenun Kubang di Kabupaten Lima Puluh Kota - Lita, Ratni Prima; Meuthia, Meuthia; Alfian, Henmaidi; Dewi, Debi Shintya (Jurnal Samudra Ekonomi dan Bisnis, 2021)
One of the creative industries that is developing in West Sumatra is the weaving craft, which is a fabric making with the simple principle of combining yarn lengthwise and transversely. The purpose of this research is to find out perceived packaging, perceived value, perceived quality dan purchase intention on Kubang H.Ridwan BY weaving in Lima Puluh Kota Regency. Descriptive type is used to find out and be able to explain the characteristics of the variables studied in a situation, with a sample size of 95 respondents. The unit of analysis in this study is consumers who have or have never transacted with Kubang H.Ridwan BY weaving, but are familiar or know about Kubang H.Ridwan BY weaving. The frequency distribution of research data is processed using Microsoft Office Excel 2007 applications. The results of the study provide several implications and recommendations for the Kubang H.Ridwan BY weaving business, so that the purchase intention of consumers and prospective consumers increases.